The rôle of formative assessment in the scriptural production of 5th year primary learners : analytical study of the teachers’ questionnaire - Timesguida, Nassima; Ait Challal , Salah (Journal of Human Sciences, 2020)
In this article, we deal with the question of formative writing assessment, which has the role in addition to improving the teaching / learning process, providing feedback and prescribing corrective measures for learners in difficulty because, it is centered on the learner and the improvement of his written production and this through approaches and approaches within the framework of an effective teaching led by qualified teachers to whom a questionnaire was drawn up and to which they had to respond because, the discussion on the formative evaluation of learning is still sometimes tainted by reluctance, false beliefs and reflections on the heaviness of the teaching task, and by answering the questionnaire we will see if the teachers are successful the process of formative evaluation with regard to improving the scriptural productions of learners in the fifth year of primary school.